Joint Constraints on Galactic Diffuse Neutrino Emission from the ANTARES and IceCube Neutrino Telescopes - Albert, A.; André, M.; Anghinolfi, M.; Ardid, M.; Aubert, J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Institute of Physics Publishing, 2018)
The existence of diffuse Galactic neutrino production is expected from cosmic-ray interactions with Galactic gas and radiation fields. Thus, neutrinos are a unique messenger offering the opportunity to test the products of Galactic cosmic-ray interactions up to energies of hundreds of TeV. Here we present a search for this production using ten years of Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) track and shower data, as well as seven years of IceCube track data. The data are combined into a joint likelihood test for neutrino emission according to the KRAg model assuming a 5 PeV per nucleon Galactic cosmic-ray cutoff. No significant excess is found. As a consequence, the limits presented in this Letter start constraining the model parameter space for Galactic cosmic-ray production and transport.